Constructing housing affordability index in Malaysia - Genesh Kumar Subramaniam; Mohd Azlan Shah Zaidi; Zulkefly Abdul Karim; Fathin Faizah Said (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to construct a housing affordability index that incorporates the financial elements namely the household income, house prices and housing lending rate. It further measure the level of housing affordability by income classifications and by states. This study also examines the extent of unaffordability among the lowest income group. We use the National Association of Realtors (NAR)-based housing affordability index that requires three clusters of data namely, the household gross income, house price, and housing loans rate. We use Malaysian data from the Department of Statistics, National Property Information Centre, and Central Bank of Malaysia. The findings show that Melaka has a high level of housing affordability, whilst Sabah had a low level of housing affordability. Meanwhile, the bottom 40 percent (B40) of income group was detected to have very poor home affordability compared to that of middle 40 percent (M40) and top 20 percent (T20) groups in Malaysia. It further capture the level of unaffordability among the B40 segment of the population, which was lacking in previous studies. This study contributes to the literature by incorporating the financial element into the formulation of the index namely, the household income, house price, and loan rate. This is to ensure that the reliability and validity of the formula developed. This research benefits various stakeholders by providing a refined and better housing affordability index that can be utilized as a benchmark for certain levels of housing affordability.